Carbimazole-induced atypia – A mimicker of malignancy in fine-needle aspiration cytology - M. Aswin Manikandan; B. Shobana; S. Marry Lilly; J. Thanka (Indian Journal of Pathology and Microbiology)
A 20-year-old female presented with complaints of thyroid swelling and showed signs and symptoms of thyrotoxicosis and fine-needle aspiration cytology (FNAC) was requested by the surgeon. On examination of FNAC smear, it showed thyroid follicular cells with atypical features like bizarre giant cells, pseudo nuclear inclusions, and mitotic figure. Correlation between clinical history and cytomorphologic features was done and it was reported as atypical changes in thyroid probably due to carbimazole-induced changes. It helped the patient, as radical surgery and its untoward complications were avoided.